Mn (II) ion coordination polymer and its preparation method and application

By introducing Mn(II) ions and specific ligands into the metal-organic framework to form Mn(II) ion coordination polymers, the problems of slow oxygen evolution reaction kinetics and insufficient catalyst efficiency in existing photocatalytic technology are solved. Efficient and stable photoelectrocatalytic performance is achieved.

CN118994628BActive Publication Date: 2025-01-24SHAANXI SCI TECH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411482881.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-24
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

The existing photocatalytics are slow in the oxygen evolution reaction (OER) process, making it difficult to effectively utilize solar energy, and the efficiency and stability of the catalyst materials are insufficient.

Method used

Adopt MN (II) ion coordinates as high-efficiency catalyst materials, and by introducing MN (II) ions and specific ligands in metal-organic skeleton, forming a three-dimensional super molecular space with distorted octophellia structure and one-dimensional chain structure Structure, improve photoelectric catalytic performance.

Benefits of technology

Mn (II) ion coordinates show high photoelectric catalytic performance under the lighting and dark conditions, which improves the efficiency and stability of oxygen analysis, so that it can be used as high -efficiency catalytic semiconductor materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118994628B_ABST
    Figure CN118994628B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of photoelectrocatalytic development technology, and in particular to a Mn (II) ion coordination polymer and a preparation method and application thereof. The present invention prepares a Mn (II) coordination polymer, the chemical expression of which is {Mn[H(5-COIA)]·3H2O} n The central Mn(Ⅱ) ion is respectively connected with H(5‑COIA) 2‑ The three oxygen atoms in the ligand (O1, O6, O7) and the oxygen atoms from the three coordinated water molecules (O8, O9, O10) form a distorted octahedral structure, and the two adjacent Mn(Ⅱ) ions are connected by H(5-COIA) 2‑ The carboxyl and hydroxyl groups of the ligands are connected to form a one-dimensional chain structure, and the one-dimensional chains form a three-dimensional supramolecular spatial structure through hydrogen bonding. The Mn (II) ion coordination polymer exhibits high photoelectrocatalytic performance both under xenon light illumination and in the dark.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photoelectrocatalysis, and in particular to a Mn (II) ion coordination polymer and a preparation method and application thereof. Background Art

[0002] With the rapid development of the global economy, the consumption of primary energy has gradually increased, especially the reserves of fossil fuels have been decreasing year by year, so the search for alternative energy and sustainable energy has become an important issue. In the process of seeking efficient and sustainable energy conversion and storage technology, photocatalysis (PEC) as a method that can directly convert solar energy into chemical energy shows great potential. Solar energy can meet our energy needs. By cleverly collecting solar energy to provide energy, solar cells decompose water through photocatalysis and convert water into hydrogen. Hydrogen, as a new energy with great development prospects, is known as the most promising new energy. Hydrocracking can be divided into oxygen evolution reaction (OER) and hydrogen evolution reaction (HER). However, the kinetics of these two reactions are slow, and OER plays a decisive role in the whole process. In order to overcome these challenges, scientists continue to explore new catalyst materials. Metal organic frameworks (MOFs), as a class of porous materials with high design ability, large specific surface area and rich pore structure, have received extensive attention in the field of photocatalytic OER in recent years.

[0003] Metal-organic framework is a new type of organic-inorganic hybrid material. MOF has the advantages of good surface regularity and large specific surface area, and has broad application prospects in the field of electrocatalysis. This material has the advantages of easy access to pores, short charge transfer distance, exposure of active centers, and smooth diffusion of reactants and products from the catalyst surface, showing excellent photocatalytic performance. The preparation of semiconductor materials is an effective way to improve their photocatalytic performance. MOF materials have unique advantages in photocatalytic oxygen evolution (OER): first, by rationally designing ligands and metal centers, it is possible to effectively utilize sunlight and improve the generation and separation of photogenerated electrons and holes; second, MOF has a large specific surface area and rich pore structure, which promotes the adsorption and diffusion of reactants on the electrode surface and accelerates the mass transfer of the OER process. On this basis, by introducing catalytically active metal sites or functional groups into the MOF skeleton, it becomes an active site for oxygen evolution reaction, thereby improving the catalytic performance of MOF, making it have great potential as an efficient catalytic semiconductor. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a Mn (II) ion coordination polymer and its preparation method and application in view of the above-mentioned deficiencies in the prior art. The crystal sample of the Mn (II) ion coordination polymer belongs to the triclinic system, the space group is P1, and the minimum asymmetric unit consists of a Mn (II) ion, a deprotonated H (5-COIA) 2- The ligand consists of three coordinated water molecules. The central Mn(Ⅱ) ion is respectively connected with H(5-COIA) 2- The three oxygen atoms (O1, O6, O7) in the ligand and the oxygen atoms (O8, O9, O10) from the three coordinated water molecules form a distorted octahedral structure, and the two adjacent Mn (II) ions are connected by H (5-COIA) 2- The carboxyl and carbonyl groups of the ligand are connected to form a one-dimensional chain structure, and the one-dimensional chains form a three-dimensional supramolecular spatial structure through hydrogen bonding.

[0005] The present invention provides a Mn (II) ion coordination polymer, wherein the chemical expression of the Mn (II) ion coordination polymer is {Mn [H (5-COIA)] · 3H2O} n , where ligand H(5-COIA) 2- is deprotonated H3(5-COIA), H3(5-COIA) is 1-(3, 5-dicarboxyphenyl)-4-oxo-1, 4-dihydropyridazine-3-carboxylic acid.

[0006] According to the Mn (II) ion coordination polymer provided by the present invention, the crystal sample of the Mn (II) ion coordination polymer belongs to the triclinic system, the space group is P1, and the minimum asymmetric unit consists of a Mn (II) ion, a deprotonated H (5-COIA) 2- The ligand consists of three coordinated water molecules, and the central Mn(Ⅱ) ion is respectively connected with H(5-COIA) 2- The three oxygen atoms (O1, O6, O7) in the ligand and the oxygen atoms (O8, O9, O10) from the three coordinated water molecules form a distorted octahedral structure, and the two adjacent Mn (II) ions are connected by H (5-COIA) 2- The carboxyl and carbonyl groups of the ligands are connected to form a one-dimensional chain structure, and the one-dimensional chains form a three-dimensional supramolecular spatial structure through hydrogen bonding.

[0007] The present invention provides a method for preparing the above-mentioned Mn (II) ion coordination polymer, comprising the following steps:

[0008] S1, adding manganese salt and H3(5-COIA) to acetonitrile to obtain a mixed solution, and the mixed solution is kept at a high temperature to fully react to obtain an intermediate product;

[0009] S2, cooling the intermediate product prepared in S1 to crystallize, and washing, filtering and drying the precipitated crystals in sequence to obtain a Mn (II) ion coordination polymer.

[0010] According to the preparation method of the Mn (II) ion coordination polymer provided by the present invention, the molar volume ratio of the manganese salt, H3 (5-COIA) and acetonitrile in S1 is 3 mmol: 1 mmol: 2 mL, and the manganese salt in S1 is manganese chloride tetrahydrate.

[0011] According to the method for preparing a Mn (II) ion coordination polymer provided by the present invention, the high temperature condition in S1 is 90 to 100° C., and the sufficient reaction time is 48 to 50 h.

[0012] According to the preparation method of the Mn (II) ion coordination polymer provided by the present invention, the washing solvent in S2 is deionized water, the filtration is reduced pressure filtration, and the drying is constant temperature drying in an oven at 30° C. for 3 to 4 h.

[0013] The present invention also provides an application of a Mn (II) ion coordination polymer, wherein the Mn (II) ion coordination polymer is used as a high-efficiency semiconductor material in photoelectrocatalysis.

[0014] The coordination polymer crystal belongs to the triclinic system, P1 space group, and the unit cell parameters are a=5.1145(6) Å, b=5.6625(7) Å, c=13.4882(15)Å, α= 89.679(2)°, β= 84.064(2)°, γ=73.773(2)°, V=372.95(8) Å 3 .

[0015] Compared with the prior art, the present invention has the following advantages:

[0016] (1) In the present invention, a manganese salt and H3(5-COIA) are added to acetonitrile to obtain a mixed solution, and a Mn(II) ion coordination polymer {Mn[H(5-COIA)]·3H2O} is prepared by a one-pot solvothermal reaction. n The preparation method has the advantages of simple process, convenient operation, a yield of 79.3% and good reproducibility.

[0017] (2) The Mn (II) ion coordination polymer of the present invention has good catalytic performance. The Mn (II) ion coordination polymer exhibits high photoelectrocatalytic performance both under xenon lamp illumination and in the dark, making it a highly efficient catalytic semiconductor material, providing new progress in the construction of new complexes and their performance in photoelectrocatalysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 is a single molecule image of the Mn(II) ion coordination polymer prepared in Example 1;

[0019] Figure 2 is a three-dimensional supramolecular structure diagram of the Mn (II) ion coordination polymer prepared in Example 1;

[0020] Figure 3 is the IR graph of the Mn (II) ion coordination polymer prepared in Example 1;

[0021] Figure 4 is the XRD pattern of the Mn(II) ion coordination polymer prepared in Example 1;

[0022] Figure 5 is the cyclic voltammetry curve of the Mn (II) ion coordination polymer prepared in Example 1 in the dark and under xenon lamp irradiation;

[0023] Figure 6 is the electrochemical impedance spectroscopy curve of the Mn (II) ion coordination polymer prepared in Example 1;

[0024] Figure 7 This is the photocurrent response curve of the Mn (II) ion coordination polymer prepared in Example 1 when irradiated with a xenon lamp on / off for 50 seconds.

[0025] Figure 8 This is the linear sweep voltammetry curve of the Mn (II) ion coordination polymer prepared in Example 1.

[0026] Fig. 9 This is the Mott-Schottky plot of the Mn (II) ion coordination polymer prepared in Example 1 under dark and xenon lamp irradiation conditions. DETAILED DESCRIPTION

[0027] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0028] Example 1

[0029] This embodiment provides a method for preparing a Mn (II) ion coordination polymer, and the specific steps are as follows:

[0030] S1, add 3 mmol of manganese chloride tetrahydrate and 1 mmol of H3(5-COIA) to 2 mL of acetonitrile to obtain a mixed solution, and carry out a solvothermal reaction in a glass scintillation vial at a temperature of 90 °C for 48 h to obtain an intermediate product;

[0031] S2, natural cooling The intermediate product prepared in S1 was washed with deionized water and filtered under reduced pressure to obtain transparent block crystals, which were then placed in an oven at 30 °C and dried for 3 h to obtain a Mn (II) ion coordination polymer {Mn[H(5-COIA)]·3H2O} n , with a yield of 79.3%.

[0032] Example 2

[0033] This embodiment provides a method for preparing a Mn (II) ion coordination polymer, and the specific steps are as follows:

[0034] S1. Add 3 mmol of manganese chloride tetrahydrate and 1 mmol of H3(5-COIA) to 2 mL of acetonitrile to obtain a mixed solution, and carry out a solvothermal reaction in a glass scintillation vial at 100 °C for 48 h to obtain an intermediate product.

[0035] S2, natural cooling The intermediate product prepared in S1 was washed with deionized water and filtered under reduced pressure to obtain transparent block crystals, which were then placed in an oven at 30 °C and dried for 4 h to obtain a Mn (II) ion coordination polymer {Mn[H(5-COIA)]·3H2O} n , with a yield of 78.9%.

[0036] Example 3

[0037] This embodiment provides a method for preparing a Mn (II) ion coordination polymer, and the specific steps are as follows:

[0038] S1, add 3 mmol of manganese chloride tetrahydrate and 1 mmol of H3(5-COIA) to 2 mL of acetonitrile to obtain a mixed solution, and carry out a solvothermal reaction in a glass scintillation vial at a temperature of 90 °C for 50 h to obtain an intermediate product;

[0039] S2, natural cooling The intermediate product prepared in S1 was washed with deionized water and filtered under reduced pressure to obtain transparent block crystals, which were then placed in an oven at 30 °C and dried for 3 h to obtain a Mn (II) ion coordination polymer {Mn[H(5-COIA)]·3H2O} n , with a yield of 75.4%.

[0040] Example 4

[0041] The Mn (II) ion coordination polymer prepared in Example 1 was characterized, and the specific characterization results are as follows:

[0042] ① Coordination polymer {Mn[H(5-COIA)]·3H2O} n Crystal structure determination:

[0043] Under a microscope, a single crystal with a suitable size of 0.200×0.230×0.250 mm was selected for X-ray diffraction experiments at room temperature. Diffraction data were collected on a Bruker-ApexП X-ray single crystal diffractometer. Mo-Kα rays (λ= 0.71073 Å) were monochromatized by a graphite monochromator, and diffraction points were collected in an ω-2θ scanning mode. All data were corrected by factors and empirical absorption, and the crystal structure was solved by a direct method using a program. Hydrogen atoms were determined by difference Fourier synthesis and fixed in the calculated optimal position. Using the SHELX-97 program, all non-hydrogen atoms and their anisotropic thermal parameters were corrected based on the full-matrix least squares method. Detailed crystal measurement data are shown in Table 1, important bond length and bond angle data are shown in Table 2, and the crystal structure is shown in Table 2. Figure 1 As shown in Figure 2, observing the three-dimensional supramolecular structure of the polymer from the c-axis direction, obvious molecular channels can be seen, such as Figure 2 shown.

[0044] Table 1 Main crystallographic data of Mn(II) ion coordination polymers

[0045]

[0046] Table 2 Important bond lengths (Å) and bond angles (°) of Mn(II) ion coordination polymers

[0047]

[0048] In Table 1, a, b and c represent the edge lengths of the crystal in the directions of the three crystal axes, respectively, and α, β and γ represent the angles between a and b, a and c, and b and c, respectively; Z is the number of molecules contained in the unit cell; the diffraction index range of the limiting factor is (h, k, l); F (000) is the number of electrons in the unit cell; Θ is the θ angle range over which the data were collected; Final R indices I >2σ( I )] is the residual factor R value for the observable diffraction point; R is the non-weighted consistency factor; R1 and wR2 are both weighted consistency factors;

[0049] In the first row of Table 2, Mn(1) refers to Mn atom 1 in the Mn(II) ion coordination polymer single crystal, O(11) refers to O atom 11 in the Mn(II) ion coordination polymer single crystal, and Mn(1)-O(11) represents the bond length between Mn atom 1 and O atom 11, which is 2.160±3, with 3 being the standard deviation;

[0050] C(2)-C(3)-C(4) represents the bond angle between C atom 2, C atom 3 and C atom 4, and its bond angle is 120.1±4;

[0051] The same applies to other data in the table.

[0052] ②IR spectrum characterization:

[0053] Figure 3 This is the IR spectrum of the Mn (II) ion coordination polymer. The sample infrared spectrum data collection range is 500-4000 cm -1 , using KBr pellets.

[0054] Depend on Figure 3 It can be seen that 1504~1621 cm -1 The peak between them is the benzene ring stretching vibration peak, 3135 cm -1 The OH bond stretching vibration peak in water molecules is 1703 cm -1 The peak is the stretching vibration peak of the carbonyl group.

[0055] The molecular formula of the Mn (II) ion coordination polymer prepared in Example 2 is {Mn[H(5-COIA)]·3H2O} n .

[0056] ③Phase purity characterization of Mn (II) ion coordination polymer:

[0057] The powder XRD characterization results of the Mn (II) ion coordination polymer using a Bruker / D8Advance X-ray diffractometer showed that it has reliable phase purity, which provides a guarantee for its application as a catalyst, such as Figure 4 shown.

[0058] ④ Photoelectrocatalytic performance of Mn (II) ion coordination polymer:

[0059] The cyclic voltammetry curves of the Mn(II) ion coordination polymer in the dark and under 50 mV / s xenon lamp irradiation show obvious redox peaks and an obvious OER process trend with increasing potential, such as Figure 5 shown.

[0060] Electrochemical impedance spectroscopy curves are used to characterize the OER interface kinetics, such as Figure 6 As shown in the figure, it can be observed that the impedance of the complex decreases, especially the impedance of the Mn (II) ion coordination polymer decreases significantly during illumination.

[0061] In addition, at a current density of 1 mA·cm -2 The photocurrent response of the Mn(II) ion coordination polymer was evaluated at a potential of 2.5 Å to assess its stability. Figure 7 As shown, the experiment was performed alternately under dark and light conditions with an interval of 50 seconds. The Mn(II) ion coordination polymer exhibited stable photocurrent during the irradiation process.

[0062] Polarization curves of the complexes were obtained at an LSV scan rate of 5 mV / s to determine the difference in overpotential required for OER in the dark and under illumination, as Figure 8 The polarization curve shows that at 1.0 mA·cm -2 At the current density, the overpotential of the Mn(II) ion coordination polymer is 726 mV (light) and 757 mV (dark).

[0063] The Mott-Schottky (MS) curve is usually used to determine the semiconductor type of the complex. Fig. 9 As shown in the figure, when the frequency is 500 Hz, 1000 Hz and 1500 Hz, the slope of the MS curve of the complex is positive, indicating that the Mn (II) ion coordination polymer is an n-type semiconductor. By linearly fitting the MS curves of these three frequencies, it was determined that the VBM of the Mn (II) ion coordination polymer is 1.51 V, which is greater than the standard potential of OER (1.23 V), showing enhanced OER catalytic activity.

[0064] The results show that the Mn(II) ion coordination polymer {Mn[H(5-COIA)]·3H2O} n It exhibits high photoelectrocatalytic performance, making it a highly efficient catalytic semiconductor material, and provides new progress in the construction of new complexes and their performance in photoelectrocatalysis.

[0065] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A Mn (II) ion coordination polymer, characterized in that: The chemical expression of the Mn (II) ion coordination polymer is {Mn[H(5-COIA)]·3H2O} n , where ligand H(5-COIA) 2- is deprotonated H3(5-COIA), wherein H3(5-COIA) is 1-(3, 5-dicarboxyphenyl)-4-oxo-1, 4-dihydropyridazine-3-carboxylic acid.

2. The Mn (II) ion coordination polymer according to claim 1, characterized in that: The crystal sample of the Mn(II) ion coordination polymer belongs to the triclinic system, the space group is P1, and the smallest asymmetric unit consists of a Mn(II) ion, a deprotonated H(5-COIA) 2- The ligand consists of three coordinated water molecules, and the central Mn(Ⅱ) ion is respectively connected with H(5-COIA) 2- The three oxygen atoms (O1, O6, O7) in the ligand and the oxygen atoms (O8, O9, O10) from the three coordinated water molecules form a distorted octahedral structure, and the two adjacent Mn (II) ions are connected by H (5-COIA) 2- The carboxyl and carbonyl groups of the ligand are connected to form a one-dimensional chain structure, and the one-dimensional chains form a three-dimensional supramolecular spatial structure through hydrogen bonding.

3. A method for preparing the Mn (II) ion coordination polymer according to any one of claims 1 to 2, characterized in that: The following steps are involved: S1. Adding manganese salt and H3(5-COIA) to acetonitrile to obtain a mixed solution, and the mixed solution is kept at a high temperature of 90 to 100° C. for 48 to 50 hours to obtain an intermediate product; S2, cooling the intermediate product prepared in S1 to crystallize, and washing, filtering and drying the precipitated crystals in sequence to obtain a Mn (II) ion coordination polymer.

4. The method for preparing the Mn (II) ion coordination polymer according to claim 3, characterized in that: The molar volume ratio of the manganese salt, H3(5-COIA) and acetonitrile in S1 is 3 mmol:1 mmol:2 mL, and the manganese salt in S1 is manganese chloride tetrahydrate.

5. The method for preparing the Mn (II) ion coordination polymer according to claim 3, characterized in that: The washing solvent in S2 is deionized water, the filtration is reduced pressure filtration, and the drying is constant temperature drying in an oven at 30° C. for 3 to 4 hours.

6. An application of the Mn (II) ion coordination polymer according to any one of claims 1 to 2, characterized in that: The Mn(II) ion coordination polymer is used as a highly efficient semiconductor material in photoelectrocatalysis.

Citation Information

Patent Citations

  • Mn (II) coordination polymer as well as preparation method and application thereof

    CN118359822A

  • Pyridazine hydrogen bond skeleton fluorescence sensing material and preparation method and application thereof

    CN118546389A